Analisis faktor-faktor yang mempengaruhi pendapatan pengrajin arang tempurung di Kabupaten Tanjung Jabung Barat (Studi kasus di Kecamatan Kuala Betara) - Muhammad, Rasidin; Achmad, Erni; Nurjanah, Rahma (Prodi Ekonomi Pembangunan Fakultas Ekonomi dan Bisnis Universitas Jambi, 2022)
The purpose of this research is to find out and analyze the characteristics of shell charcoal artisans in West Tanjung Jabung Regency and to find out and analyze the factors that influence shell charcoal artisans in West Tanjung Jabung Regency. The data used in this study is primary data. The analytical tool used is multiple linear regression. The results showed that capital, production, and working hours simultaneously had a significant effect on the income of shell charcoal artisans in Kuala Betara District, Tanjung Jabung Barat Regency. Individually, capital and production variables affect the payment of shell charcoal artisans. In contrast, working hours do not affect the income of shell charcoal artisans in Kuala Betara District, Tanjung Jabung Barat Regency.